Rescue analgesia with a transversus abdominis plane block alleviates moderate-to-severe pain and improves oxygenation after abdominal surgery: a randomized controlled trial - He, Jingxian; Qin, Shuai; Wang, Yuwen; Ye, Qiuping; Wang, Penglei; Zhang, Ye; Wu, Yun (Frontiers in Pain Research, 2024)
BackgroundAbdominal surgery is a common surgical procedure that is frequently associated with substantial postoperative pain. However, rescue analgesia using opioids is associated with several adverse effects. The transversus abdominis plane block (TAPB) has been demonstrated to be effective as part of multimodal analgesia. This study aims to evaluate the effects of rescue analgesia using the TAPB following abdominal surgery.MethodsNinety patients undergoing abdominal surgery and reporting a numeric rating scale (NRS) score of cough pain ≥4 on the first postoperative day were randomized to receive either sufentanil or TAPB for rescue analgesia. Pain scores and arterial oxygen pressure (PaO2) were evaluated before and after the administration of rescue analgesia. Sleep quality and gastrointestinal function were assessed postoperatively. The primary outcome was the degree of pain relief on coughing 30 min after the administration of rescue analgesia.ResultsPatients of both groups reported a significantly reduced NRS score on coughing 30 min after receiving rescue analgesia (Ppaired < 0.001 for both groups). Notably, the degree of pain relief was significantly higher in the TAPB group than in the sufentanil group [median (interquartile range), −3 (−4 to −2) vs. −2 (−2 to −1), median difference = −1; 95% confidence interval, −2 to −1; P < 0.001]. Moreover, patients in the TAPB group experienced less pain than those in the sufentanil group during the following 24 h. When evaluated, PaO2 increased significantly after rescue analgesia was administered in the TAPB group (Ppaired < 0.001); however, there were no significant intragroup differences in the sufentanil group (Ppaired = 0.129). Patients receiving the TAPB experienced better quality of sleep than those receiving sufentanil (P = 0.008), while no statistical differences in gastrointestinal function were observed between the two groups.ConclusionRescue analgesia with the TAPB on the first postoperative day alleviated pain, enhanced oxygenation, and improved sleep quality in patients undergoing abdominal surgery; however, its effect on gastrointestinal function requires further research.Clinical Trial RegistrationThis study was registered in the Chinese Clinical Trial Registry (https://www.chictr.org.cn/showproj.html?proj=170983, ChiCTR2200060285) on 26 May 2022: Patients were recruited during the period between 30 May 2022 and 14 February 2023, and a follow-up of the last enrolled patient was completed on 16 March 2023.